Analisa Bilangan Peroksida dan Bilangan Asam pada Minyak Goreng Pedagang Penyetan Di Sutorejo Surabaya - Mardiyah, Siti (Universitas Muhammadiyah Surabaya)
Analisa Bilangan Peroksida dan Bilangan Asam pada Minyak Goreng Pedagang Penyetan Di Sutorejo Surabaya Siti Mardiyah, S.Si., M.Kes.Prodi D3 Analis Kesehatan UM Surabaya Abstract Cooking oil is the oil derived from plants or animal fat purified, is liquid at room temperature and is typically used to fry food. Cooking oil can be used up to 3-4 times a frying pan. If used repeatedly, the oil will change color. Oil damage can occur due to various factors, one of which is the temperature or heat which becomes a standard indicator for high peroxide and acid numbers. Peroxide and acid number according to the requirements of SNI is 5.0 milligrams of oxygen per 100 gram. The aim of research to find out the levels of peroxide and acid in the cooking oil used by Penyetan traders at Sutorejo street in Surabaya.This is a descriptive research that finds out the levels of peroxide and acid in the cooking oil. The research population used is the cooking oil of Penyetan traders at Sutorejo street Surabaya, and samples of it are 36 samples taken randomly. The content analysis of peroxide and acid uses iodometric method.The result shows that there are 6 samples qualified with a percentage of 17% and 30 samples did not qualify with a percentage of 83% and 9 samples qualify percentage of 25%, 27 do not qualify with a percentage of 75% according to the SNI, National Standardization of Indonesia .Keyword: Oil, Peroxide, Acid